2015
DOI: 10.1093/jnci/djv428
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Endometrial and Ovarian Carcinomas: Evidence of Clonality

Abstract: Many women with ovarian endometrioid carcinoma present with concurrent endometrial carcinoma. Organ-confined and low-grade synchronous endometrial and ovarian tumors (SEOs) clinically behave as independent primary tumors rather than a single advanced-stage carcinoma. We used 18 SEOs to investigate the ancestral relationship between the endometrial and ovarian components. Based on both targeted and exome sequencing, 17 of 18 patient cases of simultaneous cancer of the endometrium and ovary from our series showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
111
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 27 publications
8
111
0
9
Order By: Relevance
“…Our analysis confirms that the majority of SEOC cases are diagnosed at an early stage and display synchronous endometrioid adenocarcinomas in both endometrium and ovary. Specifically, we found that 72% of EC cases and 70% of ovarian cancer cases were classified as FIGO stage I (13). Others have confirmed these findings by subjecting cancer tissue from five SEOC cases to whole-exome massively parallel sequencing, demonstrating that the endometrial and ovarian tumor cells displayed strikingly similar repertoires of somatic mutations and gene copy number alterations in all investigated cases (14).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Our analysis confirms that the majority of SEOC cases are diagnosed at an early stage and display synchronous endometrioid adenocarcinomas in both endometrium and ovary. Specifically, we found that 72% of EC cases and 70% of ovarian cancer cases were classified as FIGO stage I (13). Others have confirmed these findings by subjecting cancer tissue from five SEOC cases to whole-exome massively parallel sequencing, demonstrating that the endometrial and ovarian tumor cells displayed strikingly similar repertoires of somatic mutations and gene copy number alterations in all investigated cases (14).…”
Section: Discussionsupporting
confidence: 75%
“…In addition to these favorable clinicapthologic characteristics, the prognosis of women with SEOC seems to be better than that of women with single ovarian cancer, independent of tumor stage (5). This may be due to genetically-based restrictions of tumor dissemination in women with SEOC (13). In our analysis of survival data in the literature, the mean recurrence-free survival time of young women with SEOC was 1.9 years and the mean overall survival time was 4.0 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be interesting to determine whether post-menopausal patients would also have a less favorable prognosis. Most synchronous ovarian cancers were found to be clonally related to endometrial carcinomas, suggesting the possibility of a metastatic event 26. More importantly, these patients had a favorable prognosis, suggesting that the disseminating cells are restricted to physically accessible and microenvironmentally compatible sites, yet remain indolent without the capacity for further dissemination.…”
Section: Discussionmentioning
confidence: 99%